2021
DOI: 10.3390/catal11070764
|View full text |Cite
|
Sign up to set email alerts
|

On the Oxygen Reduction Reaction Mechanism Catalyzed by Pd Complexes on 2D Carbon. A Theoretical Study

Abstract: Oxygen Reduction Reaction (ORR) is the bottle-neck strategic reaction ruling the fuel cell efficiency process. The slow kinetics of the reaction require highly effective electrocatalysts for proper boosting. In this field, composite catalysts formed by carbon nanotubes functionalized with palladium(II) complexes showed surprising catalytic activity comparable to those of a commercial Pt electrode, but the catalytic mechanisms of these materials still remain open to discussion. In this paper, we propose the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…6b), which are in agreement with the presence of a sp 3 nitrogen atom with the lone pair available for coordination. This finding is in line with the theoretical calculations 35 already mentioned showing that O 2 is able to form an apical bond with Pd( ii ) centres. Indeed, despite the known propensity of Pd( ii ) to square planar coordination, it is possible to recover almost 150 structures from the Cambridge Structural Database showing a possibly five-coordinated Pd( ii ) ion, almost half of them showing the metal in a distorted square pyramidal environment.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…6b), which are in agreement with the presence of a sp 3 nitrogen atom with the lone pair available for coordination. This finding is in line with the theoretical calculations 35 already mentioned showing that O 2 is able to form an apical bond with Pd( ii ) centres. Indeed, despite the known propensity of Pd( ii ) to square planar coordination, it is possible to recover almost 150 structures from the Cambridge Structural Database showing a possibly five-coordinated Pd( ii ) ion, almost half of them showing the metal in a distorted square pyramidal environment.…”
Section: Resultssupporting
confidence: 93%
“…This objective is intended as an experimental verification of previous theoretical results showing that Pd( ii ) can still function as an efficient catalyst for ORR through the axial interaction of O 2 with metal centres. 35 Beyond its conceptual value, this objective has great relevance for the design and synthesis of ligands used to anchor Pd( ii ) in heterogeneous catalysts. The possibility of using macrocyclic ligands that saturate the square planar coordination environment typical of this metal ion, without the need to preserve coordination sites occupied by labile donors, greatly facilitates the preparation of these ligands and allows for stronger coordination of the metal ion with consequent enhancement of the catalyst robustness.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Despite these important advances, their commercial applications are still hampered by the slow kinetics of the oxygen reduction reaction (ORR) on the cathode. 6,7 In our previous research, we reported on the utilization of Co 3 O 4 -CeO 2 /KB, 8 Co 3 O 4 /Co-N-C, 9 and Fe 3 C@Fe/N catalysts 10 as positive electrode materials for Al-air batteries. These materials have demonstrated signicant enhancements in electrocatalytic performance for the ORR at high current densities.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the adsorption of PdCl 4 2– on these hybrids was carried out until a 1:1 ligand/Pd molar ratio was obtained, thus providing the catalysts G-L1-Pd and MWCNT-L2-Pd in which most of the Pd­(II) was adsorbed via complexation by the common macrocyclic polyamine function of the corresponding ligand. The adsorption of L1 and L2 on the carbon substrates was ensured by the π–π stacking interaction of the 6-amino-3,4-dihydro-3-methyl-5-nitroso-4-oxo-pyrimidine ligand moieties (two in L1, one in L2) with the graphene surfaces of MWCNTs and G. The use of this adhesive pyrimidine residue was initially introduced by some of us for the functionalization of activated carbon (AC) aimed at the removal of chromate anions from aqueous solutions and was later extended to the generation of new materials for further remediation purposes (cation and anion sequestration) as well as for applications in fuel cells (oxygen reduction reactions), hydrogenation processes, and the photochemical generation of hydrogen …”
Section: Introductionmentioning
confidence: 99%